Directed evolution of Oenococcus oeni strains for more efficient malolactic fermentation in a multi-stressor wine environment. (August 2018) - Jiang, Jiao; Sumby, Krista M.; Sundstrom, Joanna F.; Grbin, Paul R.; Jiranek, Vladimir
Abstract: High concentrations of ethanol, low pH, the presence of sulfur dioxide and some polyphenols have been reported to inhibit Oenococcus oeni growth, thereby negatively affecting malolactic fermentation (MLF) of wine. In order to generate superior O. oeni strains that can conduct more efficient MLF, despite these multiple stressors, a continuous culture approach was designed to directly evolve an existing ethanol tolerant O. oeni strain, A90. The strain was grown for ∼350 generations in a red wine-like environment with increasing levels of stressors. Three strains were selected from screening experiments based on their completion of fermentation in a synthetic wine/wine blend with 15.1% (v/v) ethanol, 26 mg/L SO2 at pH 3.35 within 160 h, while the parent strain fermented no more than two thirds ofl -malic acid in this medium. These superior strains also fermented faster and/or had a larger population in four different wines. A reduced or equivalent amount of the undesirable volatile, acetic acid, was produced by the optimised strains compared to a commercial strain in Mouvedre and Merlot wines. These findings demonstrate the feasibility of using directed evolution as a tool to generate more efficient MLF starters tailored for wines with multiple stressors. Highlights: A continuous culture approach was designed to optimise Oenococcus oeni over hundreds of generations of growth. A wine-like medium/wine with typical oenologically-relevant stressors was used to evolve bacteria. Effective screening methods were used to select three superior strains from hundreds of single candidate isolates. Superior strains had more growth and fermented faster than the parent strain in various wines. Superior strains produced less or equivalent amounts of acetic acid compared to a commercial O. oeni strain in two wines.